Moderasi Beragama Santri Melalui Penguatan Nilai Pendidikan Humanistik Pada Dayah Salafiyah - Muammar Muammar; Fakhrul Rijal; Tasnim Idris (Journal on Education, 2024)
Humanist education is education that reflects human integrity and helps humans to be more humane, namely helping humans to actualize their existing potential so that ultimately a complete human being is formed who has emotional maturity, moral maturity and spiritual maturity. Humanistic education in Islam is humanist-religious, where the development of life (science) cannot be separated from religious and cultural values. The development of students' potential can only be realized if the implementation of education is based on humanist principles, namely the protection of human life values, honor and dignity. The human values that teachers instill in students in learning include the value of politeness, the value of tolerance, the value of freedom, the value of cooperation and the value of sincerity. Dayah as an Islamic educational institution is required to realize this mission. This research aims to find the value of humanist education contained in the Dayah Salafiyah learning system in South Aceh. This research uses qualitative methods. This research was conducted at Dayah Ashabul Yamin and Dayah Darurrahman, Fajar City, South Aceh. The data sources are santri, teachers' councils and Dayah leaders. Data collection techniques in this research are: (1) participant-observation technique; (2) in-depth interview technique (deep interview); (3) documentation techniques; and (4) Triangulation/combination techniques, Data Analysis and Processing Techniques carried out by Data Reduction, Data Display and Data Verification. After conducting research, the author found the following results, firstly, the value of humanism in the Dayah Salafiyah learning system is religious humanism based on local wisdom. Religious humanism based on local wisdom is built on religious values and local wisdom. The value of humanistic education is the value of freedom which is tied to religious values, the value of equality and always being together in carrying out activities, brotherhood which is built based on local wisdom without looking at ethnicity and region, helping each other and caring for each other, being independent and mutual.